Polyester-PAN / PCL composite fiber aerogel and preparation method thereof

By introducing polyester staple fibers and PAN/PCL composite fibers into nanofiber aerogels to form a three-dimensional structure and a graded pore structure, the existing nanofiber aerogels are solved, and the problem that existing nanofiber aerogels cannot meet the high filtration efficiency, low resistance pressure drop and high dust capacity at the same time, achieving the improvement of the toughness and filtration performance of the aerogels.

CN119529485APending Publication Date: 2025-02-28HENAN INST OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411659070.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing nanofiber aerogels cannot meet the performance of high filtration efficiency, low resistance pressure drop and high dust capacity at the same time, and are prone to collapse and lead to reduced filtration efficiency, making it impossible to filtration of particulate matter across stages.

Method used

A polyester-PAN/PCL composite fiber aerogel is designed, and polyester staple fiber is introduced as a framework material to improve the toughness and compression resistance of the aerogel, and accurately filtration of particles of different particle sizes through three-dimensional structure and graded pore structure.

Benefits of technology

The three-dimensional structure retention ability of the aerogel is realized, which avoids the reduction in filtration performance caused by collapse, has high filtration efficiency, low resistance pressure drop and high dust capacity, and can accurately filter particulate matter in different particle sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529485A_ABST
    Figure CN119529485A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite nanofiber aerogel, in particular to polyester-PAN / PCL composite nanofiber aerogel and a preparation method thereof. Preparing a PAN (Polyacrylonitrile) nanofiber membrane and a PCL (Polycaprolactone) nanofiber membrane; preparing a suspension by taking the nanofiber membrane and polyester fibers as raw materials; and finally, uniformly stirring the suspension, pouring into a culture dish, sealing, freezing, drying and taking out to obtain the PAN / PCL composite nanofiber aerogel. According to the prepared polyester-PAN / PCL composite nanofiber aerogel, graded pore structures exist in the aerogel, and when the proportion of micron-sized polyester staple fibers to nanofibers is 1: 1, due to the fact that the content of PAN and PCL nanofibers is large, the aerogel is high in filtering efficiency, small in resistance pressure drop, high in quality factor and better in filtering performance; when the proportion of the polyester fibers to the nanofibers is fixed, the air permeability and the filtering efficiency of the aerogel have the trend of increasing along with the increase of the mass fraction of the PCL nanofibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite nanofiber aerogels, and in particular to a polyester-PAN / PCL composite fiber aerogel and a preparation method and application thereof. Background Art

[0002] Nanofiber textile technology is an emerging textile technology that emerged in the 1990s. It refers to the textile technology that studies the laws and characteristics of the movement of electrons, atoms and molecules in the space of 0.1nm to 100nm. Nanofibers have good spinnability. The surface effect and quantum size effect of nanoparticles can significantly reduce defects such as bubbles and cracks caused by the production of fibers, and can promote the combination between macromolecular fibrils and side chains; some nanoparticles can also form nanoscale geometric structures on the fiber surface, which helps to improve the function of the fiber.

[0003] Based on the characteristics of electrospun nanofiber membranes, such as high specific surface area, high porosity, reproducibility, easy surface functionalization, light weight and three-dimensional structure, nanomaterials derived from electrospun nanofibers can greatly broaden the application field of nanofiber materials. Electrospun nanofiber membranes are often used as adsorption and filtration materials. Further improvement and optimization of their specific surface area and porosity will help improve their adsorption and filtration efficiency, and will be more conducive to their efficient modification and expansion of their deep application.

[0004] PAN is a polymer material obtained by free radical polymerization of acrylonitrile monomer. It is a polymer widely used in the preparation of nanofibers. It has scalability and can be used to load other water-soluble active materials. PAN is a white powdery solid with a density of 1.14-1.15g / cm 3 PAN is a polymer fiber commonly seen in laboratories and industrial production, with excellent chemical resistance and thermal stability. During the electrospinning process, the pre-oxidation step can cause oxidation, cyclization and dehydrogenation reactions of PAN fibers, which causes addition reactions between adjacent nitrile groups between PAN molecules, thereby further changing the chain structure into a ladder structure with higher stability. PAN is widely used in electrospinning due to its excellent specific surface area, controllable pore size and other characteristics.

[0005] PAN has good spinnability, and the nanofiber membrane prepared from it has the advantages of easy modification and easy treatment. It is an ideal adsorbent for filtering and treating polluted wastewater. The huge specific surface area of ​​PAN nanofibers gives it high adsorption performance. Studies have shown that since the surface of PAN fibers has a large number of nitrile groups, various groups such as phosphonic acid, amino amidoxime, thioamide, and carboxyl groups can be introduced through chemical reactions on the surface of PAN. They can react with transition metal ions containing empty orbitals, and are widely used in the preparation of antibacterial materials, organic reaction catalysts, and heavy metal ion adsorbents.

[0006] PCL is a biodegradable, linear synthetic aliphatic polyester that is miscible with a variety of polar organic solvents and has properties such as non-toxicity and easy decomposition. PCL has good biocompatibility and biodegradability, is easy to process, has excellent thermal stability, and has high mechanical properties. It can be mixed with a variety of natural or synthetic polymers to overcome certain shortcomings of a single polymer, and can regulate the performance and structure of the copolymer. The process is simple and the cost is low. In addition, PCL has a long molecular chain, a slow degradation rate, and good permeability to small molecular weight particles.

[0007] PCL has excellent biodegradability, biocompatibility and drug permeability. Nanofiber materials have the characteristics of small pore size and large specific surface area, which can effectively achieve uniform dispersion of small molecules of antimicrobial agents. Experiments show that with the increase of spinning solution extrusion rate or the increase of PCL mass fraction in the spinning solution, the fiber diameter of electrospun nanofibers increases, the pores of the material increase, and it becomes fluffy, resulting in a decrease in filtration efficiency, but a decrease in pressure difference, that is, a decrease in filtration resistance.

[0008] The PCL / PAN composite nanofiber membrane was prepared by electrospinning technology. The overall fiber morphology of the PCL / PAN composite nanofiber membrane was good, the overall fiber diameter was small, the diameter distribution was uniform, and there was no adhesion. The fiber distribution was more concentrated, and the crystallization performance was more inclined to the crystallization performance of pure PCL nanofiber membrane. The fiber grains were small, and the fiber crystallization was more perfect compared with other composite nanofiber membranes. In terms of filtration, Bacillus subtilis was cultured using PCL / PAN composite nanofiber membrane as a carrier, and its growth was good. The bacteria were used to treat micro-polluted water, CODMn, NH 4+ The removal rates of -N and NO2--N are high, and the test results are ideal.

[0009] Due to its different uses in the field of science and technology, electrospun nanofibers have been widely studied by scientists and have become the most widely used method for producing polymer continuous nanofibers. As a new type of aerogel, polymer nanofiber-based aerogel has become a research hotspot. It has the advantages of excellent elasticity and toughness, controllable chemical composition, high specific surface area and ultra-low density.

[0010] However, existing electrospun nanofibers still have the following problems:

[0011] 1. Existing nanofibers cannot simultaneously meet the three properties of high filtration efficiency, low resistance pressure drop and high dust capacity;

[0012] 2. Existing nanofiber aerogels are prone to collapse, resulting in a significant decrease in dust holding capacity, a significant increase in resistance pressure drop, and a decrease in filtration efficiency.

[0013] 3. The existing nanofiber aerogel has a single-size structure and cannot filter particles across sizes. Summary of the invention

[0014] In order to comprehensively solve the above problems, the present invention aims to design a polyester-PAN / PCL composite fiber aerogel. The polyester staple fiber introduced as the skeleton material of the PAN / PCL composite nanofiber aerogel can effectively improve the toughness and compression resistance of the aerogel, making the aerogel less likely to collapse. The aerogel is a three-dimensional structure with graded pore structures of different sizes inside the aerogel, which can achieve accurate filtration of particles of different particle sizes, and the three-dimensional structure can also effectively increase the dust holding capacity.

[0015] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a polyester-PAN / PCL composite fiber aerogel, firstly preparing a PAN nanofiber membrane and a PCL nanofiber membrane; then using the PAN nanofiber membrane, the PCL nanofiber membrane and the polyester fiber as raw materials to prepare a suspension; finally, stirring the suspension evenly, pouring it into a culture dish, sealing it with plastic wrap, freezing it in a refrigerator, then piercing a number of small holes in the plastic wrap wrapped around the culture dish, horizontally placing the culture dish in a vacuum freeze dryer, freeze-drying it and taking it out to obtain a PAN / PCL composite nanofiber aerogel.

[0016] Preferably, the polyester fiber size in the polyester-PAN / PCL composite fiber aerogel is micron-sized.

[0017] Preferably, the sizes of PAN fibers and PCL fibers in the polyester-PAN / PCL composite fiber aerogel are nanoscale.

[0018] A second aspect of the present invention provides a method for preparing a polyester-PAN / PCL composite fiber aerogel, comprising:

[0019] Step 1: Prepare PAN nanofiber membrane and PCL nanofiber membrane respectively;

[0020] Step 2: using PAN nanofiber membrane, PCL nanofiber membrane and polyester fiber as raw materials to prepare a suspension;

[0021] Step 3: Stir the suspension in step 2 evenly, pour it into a culture dish, seal it with plastic wrap, put it in a refrigerator, freeze it, then poke a few small holes in the plastic wrap wrapped around the culture dish, put the culture dish horizontally into a vacuum freeze dryer, take it out after freeze drying, and obtain PAN / PCL composite nanofiber aerogel.

[0022] Preferably, step 1 comprises:

[0023] Step 1.1: Pour PAN powder and MgO NPs into a sealed bottle with weighed DMF solvent and stir at 1700 r / min for 24 h to obtain a uniform PAN solution;

[0024] Step 1.2: Take PCL powder and pour it into a sealed bottle with weighed DMF solvent, stir to obtain a uniform PCL solution;

[0025] Step 1.3: The PAN solution prepared in step 1.1 is electrospun into a PAN nanofiber membrane, and the PCL solution prepared in step 1.2 is electrospun into a PCL nanofiber membrane.

[0026] Preferably, in step 1.1, the mass ratio of PAN powder, DMF and MgO NPs is 6:43:1, and the mass fraction of PAN solution is 12%.

[0027] Preferably, in step 1.2, the mass ratio of PCL powder, DMF and DCM is 5:6:14, and the mass fraction of PCL solution is 20%.

[0028] Preferably, in step 1.3, stirring is performed at a speed of 1700 r / min for 24 h.

[0029] Preferably, in step 2, the mass ratio of polyester fiber to PAN nanofiber membrane and PCL nanofiber membrane is 1:1 or 2:1, and the mass ratio of PAN nanofiber membrane to PCL nanofiber membrane is any ratio of 1:2, 2:1 or 1:1.

[0030] A third aspect of the present invention provides an application of polyester-PAN / PCL composite fiber aerogel for preparing an air purification filter element.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The polyester staple fiber introduced as the skeleton material of PAN / PCL composite nanofiber aerogel can effectively improve the toughness and compression resistance of the aerogel, making the aerogel less likely to collapse, and thus having a good three-dimensional structure retention ability, thus avoiding a significant decrease in filtration performance after collapse.

[0033] 2. There are PAN nanofibers and PCL nanofibers in the aerogel. The microscopic morphology, diameter, and chemical groups of the two fibers are different. PAN / PCL composite nanofiber aerogel can utilize the different fiber diameters, different surface polar groups, different electrostatic adsorption properties, and different biodegradability of the two fibers. The physical and chemical properties are better and the application range is wider.

[0034] 3. The aerogel is composed of polyester micron-sized short fibers, nano-sized PAN and PCL fibers entangled and stacked to form a three-dimensional structure. The aerogel has a graded pore structure of different sizes, which can achieve accurate filtration of particles of different sizes. In addition, the three-dimensional structure can also effectively increase the dust holding capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0036] In the attached picture:

[0037] Figure 1 PAN (left) and PCL (right) nanofiber membranes;

[0038] Figure 2 Actual pictures of polyester-PAN and PCL nanofiber aerogel, Figure 2 Among them, (a) sample 1; (b) sample 2; (c) sample 3; (d) sample 4; (d) sample 5; (d) sample 6;

[0039] Figure 3 The scanning electron microscope images of PAN and PCL nanofiber membranes are shown in Figure 2. Figure 3 In, (a) PAN (b) PCL;

[0040] Figure 4 This is a scanning electron microscope image of nanofiber aerogel. Figure 4 Among them, (a) SEM image of sample 1 (b) SEM image of sample 3; (c) SEM image of sample 5 (d) SEM image of sample 2; (e) SEM image of sample 4 (f) SEM image of sample 6;

[0041] Figure 5 is the average diameter and standard deviation of the nanofibers of each sample;

[0042] Figure 6 It is the infrared spectra of each sample of the present invention;

[0043] Figure 7 Air permeability of different nanofiber aerogels;

[0044] Figure 8Filtration efficiency and resistance pressure drop of different nanofiber aerogels;

[0045] Fig. 9 Quality factors of different nanofiber aerogels;

[0046] Fig.10 is a flow chart of the preparation method of the present invention;

[0047] Fig.11 The first compression performance test results of each sample;

[0048] Fig.12 The first compression performance test results of samples 1, 3, and 5;

[0049] Fig.13 The first compression performance test results of samples 2, 4, and 6;

[0050] Fig.14 Aerogel water contact angle-time diagram when polyester fiber: nanofiber = 1:1;

[0051] Fig.15 Aerogel water contact angle-time diagram when polyester fiber: nanofiber = 2:1. DETAILED DESCRIPTION

[0052] The following combination Figure 1-Figure 15 The preferred embodiments of the present invention are described. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0053] Polyacrylonitrile (PAN, analytical grade, Guangzhou Weida Fine Materials Co., Ltd.) has an average molecular weight of 85,000, no special odor, white powder, insoluble in water, easily soluble in organic solvents such as DMF, and stable chemical properties.

[0054] Polycaprolactone (PCL, analytical grade, Shunjie Plastic Technology Co., Ltd.) has an average molecular weight of 80,000, no special odor, and is a white opaque solid powder. It is insoluble in water and easily soluble in various polar organic solvents such as dichloromethane.

[0055] N,N-Dimethylformamide (DMF, analytical grade, Tianjin Shengao Chemical Reagent Co., Ltd.) is a colorless or slightly yellow liquid with good hygroscopicity and stability. It is slightly soluble in benzene and can be miscible with various organic solvents such as water, ethanol, methanol, chloroform, etc. in any proportion. It can dissolve a variety of polymers.

[0056] Dichloromethane (DCM, analytical grade, Tianjin Shengao Chemical Reagent Co., Ltd.). It has a pungent aromatic odor, is volatile, is colorless and transparent, is slightly soluble in water, is miscible with most commonly used organic solvents, and is miscible with N,N-dimethylformamide in any proportion.

[0057] Magnesium oxide particles (MgO NPs, average particle size 40nm, Hangzhou Zhitai Purification Technology Co., Ltd.). White granular solid, odorless, chemically unstable, cannot be exposed to the air for a long time.

[0058] Embodiment 1:

[0059] A polyester-PAN / PCL composite fiber aerogel comprises the following steps: firstly preparing a PAN nanofiber membrane and a PCL nanofiber membrane; then taking the PAN nanofiber membrane, the PCL nanofiber membrane and polyester fiber as raw materials to prepare a suspension; finally, stirring the suspension evenly, pouring it into a culture dish, sealing it with a plastic wrap, freezing it in a refrigerator, then piercing a plurality of small holes in the plastic wrap wrapping the culture dish, horizontally placing the culture dish into a vacuum freeze dryer for freeze drying and then taking it out to obtain the PAN / PCL composite nanofiber aerogel.

[0060] Among them, the size of polyester fibers in polyester-PAN / PCL composite fiber aerogel is micron-sized, and the size of PAN fibers and PCL fibers in polyester-PAN / PCL composite fiber aerogel is nano-sized, and the diameters and surface morphologies of the two fibers are also different. Polyester-PAN / PCL composite fiber aerogel has the characteristics of light weight and high porosity. The micron polyester staple fibers in polyester-PAN / PCL composite fiber aerogel serve as the skeleton of the aerogel, which can support the entire aerogel and maintain the overall structure of the aerogel; the nano-scale diameters of PAN fibers and PCL fibers can maintain the good filtration performance of the aerogel. The aerogel has a hierarchical pore structure, and the polyester micron staple fibers are entangled with the nano-scale PAN fibers and PCL fibers to form a primary pore structure with larger pores; the nano-scale PAN fibers and PCL fibers are entangled to form a secondary pore structure with smaller pores.

[0061] In addition, the composite fiber aerogel has a hierarchical pore structure, which is formed by the entanglement of micron-sized polyester fibers with PAN fibers and PCL fibers.

[0062] Embodiment 2:

[0063] A method for preparing polyester-PAN / PCL composite fiber aerogel, comprising:

[0064] Step 1: preparing PAN nanofiber membrane and PCL nanofiber membrane respectively; comprising:

[0065] Step 1.1: 12 g PAN powder and 2 g MgO NPs were poured into a sealed bottle containing 86 g DMF solvent and stirred at 1700 r / min for 24 h to obtain a uniform PAN solution with a mass fraction of 12%;

[0066] Step 1.2: Pour 20 g PCL powder and 56 g DCM into a sealed bottle containing 24 g DMF solvent and stir to obtain a uniform PCL solution with a mass fraction of 20%;

[0067] Step 1.3: The PAN solution with a mass fraction of 12% prepared in step 1.1 is electrospun into a PAN nanofiber membrane, and the PCL solution with a mass fraction of 20% prepared in step 1.2 is electrospun into a PCL nanofiber membrane.

[0068] Test instruments: The instruments used in the test are shown in Table 1

[0069] Table 1 Test instruments and models

[0070]

[0071] Note: In addition, this test also requires glass rods, foam pads, 10ml syringes, needles, non-woven fabrics, tape, sealed bags and other items.

[0072] Take 12% PAN solution as an example. On the electrospinning device, first, take a 35cm*35cm non-woven fabric or tin foil and stick it on the roller receiver in front of the injection pump. Use a 10ml syringe to suck out about 5ml of the prepared solution. Fix the syringe on the injection pump, adjust the injection pump height to be consistent with the roller, adjust the position of the syringe needle to make it 15cm away from the collection device, and turn on the roller to rotate the roller; secondly, put a piece of paper under the syringe needle to prevent droplets from contaminating the operating table. Turn on the injection pump switch, press the "Start" button, ensure that the solution can flow out of the needle smoothly, adjust the flow rate of the injection pump to 1ml / h, and then press the "Start" button to prepare for spinning; after the circuit is correct, turn on the high-voltage DC power switch, adjust the voltage to 15kV, and start spraying. Wait for about 4 hours. After the spinning time is over, remove the non-woven fabric with nanofibers collected, place it in the air to dry for 1-2 days, cut it and put it into a sealed bag for use.

[0073] Use the same method to spin the PCL solution into PCL nanofiber membrane for later use.

[0074] The prepared PAN and PCL nanofiber membranes are Figure 1 shown.

[0075] Step 2: using PAN nanofiber membrane, PCL nanofiber membrane and polyester fiber as raw materials to prepare a suspension;

[0076] The raw materials required for this step are polyester fibers, which are milky white and mercerized. In this experiment, polyester is added to increase the toughness of the aerogel. Polyvinyl alcohol (PVA, analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.). White granular solid, odorless, soluble in water, used as an adhesive in this experiment. Deionized water refers to pure water after the impurities in ionic form are removed, which is used as a dispersion in this experiment.

[0077] In order to test the differences in various properties of aerogels prepared from different proportions of polyester fibers and nanofibers and different concentrations of PAN and PCL, the dispersion volume was 100 ml, and the suspension sample with a fiber solid mass to solvent ratio of 1:99 was prepared according to the following ratio:

[0078] Sample 1: polyester fiber: nanofiber = 1:1, PAN: PCL = 1:1, that is, the polyester fiber is 0.5g, the PAN is 0.25g, and the PCL is 0.25g.

[0079] Sample 3: polyester fiber: nanofiber = 1:1, PAN: PCL = 2:1, that is, the polyester fiber is 0.5g, PAN is 0.33g, and PCL is 0.17g.

[0080] Sample 5: polyester fiber: nanofiber = 1:1, PAN: PCL = 1:2, that is, the polyester fiber is 0.5g, the PAN is 0.17g, and the PCL is 0.33g.

[0081] Sample 2: polyester fiber: nanofiber = 2:1, PAN: PCL = 1:1, that is, the polyester fiber is 0.66g, the PAN is 0.17g, and the PCL is 0.17g.

[0082] Sample 4: polyester fiber: nanofiber = 2:1, PAN: PCL = 2:1, that is, the polyester fiber is 0.66g, PAN is 0.227g, and PCL is 0.113g.

[0083] Sample 6: polyester fiber: nanofiber = 2:1, PAN: PCL = 1:2, that is, the polyester fiber is 0.66g, PAN is 0.113g, and PCL is 0.227g.

[0084] The preparation method is:

[0085] Step 2.1: Cut the PAN and PCL nanofiber membranes into pieces, cut the polyester fibers into fiber fragments with a length of less than 1 mm, and then weigh the required grams of the sample. Put the fiber fragments into a beaker with a capacity of 200 ml, add 0.5 g of polyvinyl alcohol, and finally pour deionized water to 100 ml. Let it stand for 24 hours to allow the solute to fully blend with the solution so that the suspension can be stirred more smoothly.

[0086] Step 2.2: After 24 hours, place the solution under the blade of the high-speed homogenizing shearing machine. After fixing the beaker steadily, the blade enters the solution. After making sure there is room for stirring and there is no contact with the beaker, turn on the shearing machine with an initial speed of 3000r / min. Slowly rotate the knob to 10000r / min. After stirring for 5 minutes, slowly rotate the knob to 3000r / min again, turn off the machine, and use tweezers or other tools to clamp the fiber clamped in the gap of the blade back into the solution to reduce experimental errors.

[0087] Step 2.3: After the beaker has cooled, repeat the above steps to stir again, repeat 2-3 times until there is no large solute accumulation in the suspension, remove the beaker, remove the blade, clean the blade with deionized water, and stir the next sample as above until all 6 samples have been stirred.

[0088] Step 2.4: Place the suspension in an ultrasonic cleaner and ultrasonicate for 20 min to obtain a uniformly dispersed suspension.

[0089] Step 3: Stir the suspension in step 2 evenly, pour it into a culture dish, seal it with plastic wrap, put it in a refrigerator, and freeze it for 48 hours. Then, poke several small holes in the plastic wrap wrapped around the culture dish, put the culture dish horizontally into a vacuum freeze dryer, and take it out after freeze drying for 48 hours to obtain polyester-PAN / PCL composite nanofiber aerogel.

[0090] The final aerogel is Figure 2 The mass, diameter, thickness and volume data of the aerogel are shown in Table 2.

[0091] Table 2 Data of mass, diameter and thickness of each sample

[0092]

[0093] Experimental results:

[0094] 1. Analysis of aerogel density and porosity

[0095] Table 3 Data of aerogel density, volume mass density and porosity of each sample

[0096]

[0097] From the analysis table, it can be seen that aerogels all exhibit high porosity and low density, and with the increase of PAN content, the porosity of aerogel increases. This is because the density of PAN is smaller than that of PCL, that is, the mass of PAN per unit volume is smaller than that of PCL, that is, there are more pores, so with the increase of PAN content, the porosity of the sample increases.

[0098] 2. Scanning Electron Microscope Analysis

[0099] 2.1 Figure 3 This is a scanning electron microscope image of PAN and PCL nanofiber membranes magnified 10,000 times.

[0100] Depend on Figure 3 It can be seen that the surface of PAN nanofibers is uniform and smooth, without beading phenomenon, and the diameter of the fibers is relatively consistent. Although PCL nanofibers have a uniform and smooth surface, they have some beading phenomenon and the diameter of the fibers is uneven.

[0101] The diameters of PAN and PCL nanofibers were measured using Image J software. 50 fibers were randomly selected for measurement, and the average diameter and standard deviation of the diameter were calculated. The results are shown in Table 4.

[0102] Table 4 Average diameter and standard deviation of diameter of PAN and PCL

[0103]

[0104] It can be seen from Table 4 that the average diameter of PAN nanofibers is 245 nm, and the standard deviation of diameter is only 78 nm, indicating that the diameter of PAN nanofibers is relatively uniform, while the average diameter of PCL nanofibers is 321 nm, and the standard deviation of diameter is 153 nm, indicating that the diameter distribution of PCL nanofibers is uneven.

[0105] 2.2 SEM results and analysis of nanofiber aerogel

[0106] Figure 4 These are scanning electron microscope images of aerogel samples 1, 3, 5, 2, 4, and 6, where ①, ②, ③, and ④ in each image are electron microscope images of aerogels magnified 300, 1000, 3000, and 5000 times, respectively. The fibers in ③ are all polyester fibers, and the fibers in ④ are all nanofibers.

[0107] By observing and comparing the electron microscope images ① in each figure, it can be seen that the prepared aerogel is a three-dimensional porous network structure, and the three components can be clearly marked, namely, micron-scale pores, polyester fibers, and nanofibers. The pore structure is mainly micron-scale large pores, and the fibers are arranged in a disorderly and criss-cross manner, which makes the aerogel pores of different sizes and uneven distribution; observing ③ in each figure, the nanofibers are adhered to the polyester fibers, and it can be seen that the diameter and length of the nanofibers are very different from those of the polyester fibers; observing ④ in each figure, it can be seen that there are also many small pores between the nanofibers, and these pores are nanoscale pores, and the diameters of the nanofibers appearing in the figure are different, the larger diameter is PCL, and the smaller diameter is PAN.

[0108] By comparing Figure ④ of samples 1, 3, 5 with samples 2, 4, 6, it can be found that with the increase of PCL content, the proportion of fibers with thicker diameters increases, and the distance between nanofibers increases, and the number of pores increases. This is because the diameter of PCL nanofibers is larger, resulting in increased fiber unevenness and increased pores. It is worth noting that Figure 4 (f) There are large pieces of non-fibrous adhesive components in ①, which are presumably the added PVA adhesive.

[0109] The diameters of the polyester fibers in Figure ③ and the nanofibers in Figure ④ of each sample were measured using Image J software. By measuring the diameters of each segment of the polyester fibers in each sample, the average diameters of the polyester fibers of each sample were obtained as shown in Table 8; 50 fibers were randomly selected from Figure ④ of each sample to measure their diameters, and the average diameter and standard deviation of the diameter of each sample were obtained, as shown in Table 8. Figure 5 shown.

[0110] Table 8 Average diameter of polyester fibers

[0111]

[0112] From Table 8, it can be calculated that the average diameter of polyester fiber is 15.911 μm.

[0113] pass Figure 5 It can be seen that PAN:PCL = 1:2, that is, the average diameter of samples 5 and 6 is the largest, and the diameter standard deviation is also the largest; secondly, PAN:PCL = 1:1, that is, the average diameter and diameter standard deviation of samples 1 and 2 are both at an intermediate level; finally, PAN:PCL = 2:1, that is, the average diameter of samples 3 and 4 is the smallest, and the diameter standard deviation is also the smallest. This is because the diameter of PCL nanofibers is larger than that of PAN nanofibers, and compared with PAN fibers, the diameter of PCL fibers is uneven, so as the proportion of PCL increases, the average diameter of nanofibers in aerogel increases, but the diameter distribution is uneven, resulting in an increase in the diameter standard deviation.

[0114] 3. Aerogel infrared spectrum test results and analysis

[0115] The test results were sorted to obtain the infrared spectrum of PAN / PCL composite nanofiber aerogel, as shown in Figure 6 shown.

[0116] from Figure 6 It can be seen that at 674cm -1 、1241cm -1 、1437cm -1 、1576cm -1 、1726cm -1 、2247cm -1 、2356cm -1 、2940cm-1 、3364cm -1 、3864cm -1 There are 10 significant characteristic peaks.

[0117] For polyester fiber, 674cm -1 It is the vibration of six hydrogen atoms on the benzene ring of polyester fiber; 1241cm -1 The strong absorption peak at 1437cm is the antisymmetric stretching vibration of CO on polyester fiber; -1 、2940cm -1 The characteristic peak of corresponds to the stretching vibration of -CH in polyester fiber. Since the vibration characteristic peaks of -CH bond of polyester fiber, PAN and PCL meet, these two peaks show a blunt absorption peak with smaller intensity. The more obvious peak is 1726cm -1 The characteristic peak at 2356cm corresponds to the stretching vibration of the carbonyl C=O on the ester group of polyester fiber; -1 The characteristic peak at 3364cm corresponds to the hydrogen bond stretching vibration between carboxyl groups in polyester fibers; -1 It is the stretching vibration peak of the hydroxyl -OH of the polyester fiber. Since the vibration characteristic peaks of the hydrogen-oxygen bond of the polyester fiber and the MgO NPs meet, the peak at this point shows a blunt absorption peak with smaller intensity.

[0118] For PAN fibers, at 1437 cm -1 、2940cm -1 The relatively gentle characteristic peak corresponds to the stretching vibration of the methine -CH in PAN nanofibers; since polyacrylonitrile is prepared by copolymerization of vinyl acetate and acrylonitrile, the more obvious peak 1726cm -1 The characteristic peaks at 2247 cm correspond to the stretching vibration of carbonyl C=O on the ester group of PAN nanofibers; the most obvious one is 2247 cm -1 The characteristic peak at corresponds to the stretching vibration of the nitrile group -CN of PAN.

[0119] For PCL fiber, at 1437cm -1 、2940cm -1 The relatively gentle characteristic peaks correspond to the stretching vibration of the methine -CH in PCL nanofibers; 3864cm -1 The peak at corresponds to the stretching vibration of -OH in plasma water.

[0120] For MgO NPs, 1576 cm -1 The peak at 3364 cm is the stretching vibration of the carboxylic acid bond. -1 The peak at is the stretching vibration of the hydrogen-oxygen bond.

[0121] 4. Aerogel permeability test results and analysis

[0122] After testing, the air permeability of each sample is 268mm / s, 315mm / s, 195mm / s, 268mm / s, 256mm / s, and 469mm / s respectively. The experimental results are sorted out and the air permeability change graph of each sample is drawn. Figure 7 shown.

[0123] Since nanofiber aerogel has a large volume and a very high porosity, and contains through pores inside the aerogel, its air permeability is particularly good.

[0124] The test results show that when the ratio of polyester fiber to nanofiber is fixed, the air permeability of aerogel increases with the increase of PCL ratio. This may be because the fiber diameter of PCL nanofiber is relatively coarse and the fiber diameter distribution is uneven, which leads to the increase of aerogel pore size and air permeability.

[0125] 5. Aerogel filtration performance test results and analysis

[0126] Figure 8 is the line graph of filtration efficiency and resistance pressure drop of each sample. After calculation, the quality factor line graph of each sample is obtained, such as Fig. 9 shown.

[0127] Since aerogel has a high porosity, the resistance pressure drop is small, but there are many through pores in aerogel, so the filtration efficiency is poor.

[0128] Depend on Figure 8 From the filtration efficiency in Figure 9 and the quality factor data in Figure 9, it can be seen that the filtration efficiency of samples 1, 3, and 5 is relatively high, the resistance pressure drop is relatively small, and the quality factor is relatively high. This is mainly because the content of micron polyester staple fibers in samples 1, 3, and 5 is relatively low, and the mass ratio of micron polyester staple fibers to nanofibers is 1:1. The proportion of smaller pores formed by the entanglement of nanofibers in the prepared aerogel is relatively large, which has a greater barrier effect on particulate matter and a higher filtration efficiency. Under a certain ratio of polyester fibers to nanofibers, with the increase of the mass fraction of PAN nanofibers in the aerogel, the filtration efficiency tends to decrease, that is, in the filtration effect of PAN / PCL nanofiber aerogel, PCL dominates. This may be because the diameter of PCL nanofibers is uneven, and the coarser and finer fibers are entangled with each other to form inconsistent pore sizes, which can block both large and small particles, and can increase the barrier filtration of particles to a certain extent.

[0129] Depend on Figure 8From the resistance pressure drop data, we can see that the resistance pressure drop of samples 1, 3, and 5 is relatively low, mainly because the content of micron polyester staple fibers in samples 1, 3, and 5 is relatively low. It can be seen that the contribution of nanofibers to filtration performance in polyester-PAN / PCL aerogel is higher than that of micron-grade polyester staple fibers. Under a certain ratio of polyester fibers to nanofibers, as the mass fraction of PAN nanofibers in aerogel increases, the resistance pressure drop tends to increase. This is mainly because the diameter of PAN nanofibers is smooth and uniform, while the diameter of PCL nanofibers varies greatly. When the mass fraction of PCL nanofibers is higher, the aerogel formed is also more fluffy, the pressure difference of gas passing through becomes smaller, and the filtration resistance is reduced.

[0130] 6. Aerogel compression performance test results and analysis

[0131] Integrate the first compression test results of each sample to obtain Fig.11 The first compression test results of samples 1, 3, and 5 were integrated to obtain Fig.12 The first compression test results of samples 2, 4, and 6 are integrated to obtain Fig.13 shown.

[0132] Aerogel has the properties of ultra-high elasticity, high compressibility and recoverability due to its porous internal microstructure.

[0133] In addition, the test found that as the number of compressions increased, the load of each sample remained almost unchanged, indicating that multiple compressions did not damage the spatial structure of the aerogel, and the aerogel could basically return to its original state and had good compression resilience. That is, the compression resilience of the sample was good.

[0134] Depend on Fig.11 It can be seen that the compression rebound performance of sample 4>sample 3>sample 2>sample 6>sample 1>sample 5, that is, the compression rebound performance of the samples with polyester fiber:nanofiber=2:1 is generally greater than that of the samples with polyester fiber:nanofiber=1:1. This may be because the compression rebound performance of polyester fiber is higher than that of PAN and PCL nanofiber. The more polyester fibers, the better the compression rebound performance of the aerogel.

[0135] Depend on Fig.12It can be seen that the compression rebound performance of sample 3 (PAN fiber: PCL fiber = 2:1) > sample 1 (PAN fiber: PCL fiber = 1:1) > sample 5 (PAN fiber: PCL fiber = 1:2), that is, with the increase of PAN nanofiber content, the compression rebound performance of aerogel gradually increases. This may be because the compression rebound of PAN nanofiber is higher than that of PCL nanofiber. Secondly, the density of PAN is less than that of PCL, that is, when the weight is constant, PAN has a larger volume than PCL, a higher porosity, more connections between pores, and is easier to deform and rebound. The more PAN nanofiber content, the better the compression rebound of aerogel.

[0136] observe Fig.13 , compression rebound performance sample 4 (PAN fiber: PCL fiber = 2:1) > sample 2 (PAN fiber: PCL fiber = 1:1) > sample 6 (PAN fiber: PCL fiber = 1:2), obviously, Fig.10 The results show that the compression rebound performance of aerogels increases with the increase of PAN nanofiber content.

[0137] Through Fig.12 , 13 From the analysis, it can be concluded that because the compression resilience of PAN nanofibers is higher than that of PCL nanofibers and the density of PAN is lower than that of PCL, the more PAN nanofiber content there is, the better the compression resilience of the aerogel.

[0138] 7. Aerogel wetting performance test results and analysis

[0139] The test results are collated to obtain the wetting properties of different samples, such as Fig.14 , 15 shown.

[0140] Depend on Fig.12 , 13 It can be seen that the initial water contact angle of PAN / PCL nano-aerogel is greater than 100°, showing hydrophobicity, but after only 1s, the water contact angle decreases to below 70°, indicating that the aerogel has strong wettability. There are three main reasons for this: first, the aerogel has high porosity, many pores, and many connected pores, so it has good wettability; second, the polar group has good hydrophilicity, PAN has polar group nitrile group, PCL has polar group ester group; finally, the diameter of PAN and PCL nanofibers is small, and the capillary action of the aerogel also helps the infiltration of water droplets.

[0141] Compared with pure PAN nanofiber membrane. By comparison, when polyester fiber: nanofiber = 1:1, the wetting performance is sample 1 (PAN: PCL = 1:1) > sample 5 (PAN: PCL = 1:2) > sample 3 (PAN: PCL = 2:1), that is, when PAN: PCL is 1:1, the wetting effect is the best; when polyester fiber: nanofiber = 2:1, the wetting performance is sample 6 (PAN: PCL = 1:2) > sample 2 (PAN: PCL = 1:1) > sample 4 (PAN: PCL = 2:1), that is, when PAN: PCL is 1:2, the wetting effect is the best. From the above results, it can be seen that the PCL content has a certain relationship with the wetting performance of the aerogel. With the increase of PCL content, the wetting effect has a certain degree of increase. This may be because the polarity of the ester group in PCL is greater than the polarity of the nitrile group in PAN, and the functional group with large polarity has good hydrophilicity.

[0142] in conclusion:

[0143] (1) Through the calculation of aerogel density and porosity, it is concluded that aerogels all show high porosity and low density, and with the increase of PAN content, the porosity of aerogel increases. This is because the density of PAN is smaller than that of PCL, that is, the mass of PAN per unit volume is smaller than that of PCL, that is, there are more pores, so with the increase of PAN content, the porosity of the sample increases;

[0144] (2) The microscopic morphology of different aerogels was observed using a scanning electron microscope, and it was found that each aerogel sample had a distinct structural composition - pores, polyester fibers, and nanofibers. By calculating the diameter of the nanofiber membrane, it was concluded that the average diameter of PAN was 245nm, and the diameter distribution was relatively uniform. The average diameter of PCL was 321nm, but the fiber diameter distribution was uneven. For aerogels, as the proportion of PCL increased, the average diameter of the nanofibers in the aerogel increased, but due to the uneven distribution of PCL diameter, the standard deviation of the diameter increased;

[0145] (3) The infrared spectra of different aerogel samples show the characteristic peaks of polyester, PAN nanofibers and PCL nanofibers. -1 、1241cm -1 、1437cm -1 、1726cm -1 、2356cm -1 and 2940cm -1 , is the characteristic peak of polyester fiber; 1437cm -1 、1726cm -1 、2247cm -1 and 2940cm -1 It is the characteristic peak of PAN nanofiber; 1437cm -1 、2940cm-1 and 3864cm -1 It is the characteristic peak of PCL nanofibers;

[0146] (4) When the ratio of polyester fiber to nanofiber is fixed, the air permeability of the aerogel increases to a certain extent with the increase of PCL ratio. This may be because the fiber diameter in the PCL nanofiber membrane is relatively coarse and the fiber diameter distribution is uneven, resulting in a larger pore size of the fiber membrane and an increase in air permeability;

[0147] (5) Due to the high porosity of aerogel, the resistance pressure drop is small (the resistance pressure drop of the six aerogel samples is 16.8Pa~21.9Pa), but due to the low fiber mass density in the aerogel and the large number of through pores inside, the filtration efficiency is poor (the filtration efficiency of the six aerogel samples is 75.04%~91.56%). When the content of polyester staple fibers in the aerogel is low, the filtration performance of the aerogel is better and the quality factor is higher. When the polyester fiber and nanofiber have a certain ratio, as the mass fraction of PCL nanofibers in the aerogel increases, the filtration efficiency tends to increase and the resistance pressure drop tends to decrease.

[0148] (6) Aerogel has ultra-high elasticity, high compressibility and recoverability due to its porous internal microstructure. As the number of compressions increases, the load of each sample remains almost unchanged, indicating that multiple cycles of compression have not destroyed the spatial structure of the aerogel. The aerogel basically recovers to its original state and maintains good elastic properties. That is, the sample has good compression resilience. The compression resilience of samples with polyester fiber: nanofiber = 2:1 is generally greater than that of samples with polyester fiber: nanofiber = 1:1. This may be because the compression resilience of polyester fiber is higher than that of PAN and PCL nanofibers. The more polyester fibers, the better the compression resilience of the aerogel. Because the compression resilience of PAN nanofibers is higher than that of PCL nanofibers, and the density of PAN is lower than that of PCL, the more PAN nanofibers, the better the compression resilience of the aerogel.

[0149] (7) The initial water contact angle of the aerogel is greater than 100°, showing hydrophobicity, but after only 1 second, the water contact angle decreases to below 70°, indicating that the aerogel has strong wettability. There are three main reasons for this: first, the aerogel has a high porosity, many pores, and many interconnected pores, so it has good wettability; second, the polar groups are hydrophilic, PAN contains polar groups such as nitrile groups, and PCL contains polar groups such as ester groups; finally, the diameters of PAN and PCL nanofibers are small, and the capillary action of the aerogel also helps the infiltration of water droplets.

[0150] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A polyester-PAN / PCL composite fiber aerogel, characterized in that: First, PAN nanofiber membrane and PCL nanofiber membrane are prepared; then, the PAN nanofiber membrane, PCL nanofiber membrane and polyester fiber are used as raw materials to prepare a suspension; finally, the suspension is stirred evenly, poured into a culture dish, sealed with plastic wrap, and frozen in a refrigerator, and then a number of small holes are pierced in the plastic wrap wrapped around the culture dish, and the culture dish is horizontally placed in a vacuum freeze dryer for freeze drying and then taken out to obtain polyester-PAN / PCL composite fiber aerogel.

2. The polyester-PAN / PCL composite fiber aerogel according to claim 1, characterized in that: The polyester fiber size in the polyester-PAN / PCL composite fiber aerogel is micron-sized.

3. The polyester-PAN / PCL composite fiber aerogel according to claim 2, characterized in that: The sizes of PAN fibers and PCL fibers in polyester-PAN / PCL composite fiber aerogel are nanoscale.

4. A method for preparing polyester-PAN / PCL composite fiber aerogel, characterized in that: include: Step 1: Prepare PAN nanofiber membrane and PCL nanofiber membrane respectively; Step 2: using PAN nanofiber membrane, PCL nanofiber membrane and polyester fiber as raw materials, preparing a suspension; Step 3: Stir the suspension in step 2 evenly, pour it into a culture dish, seal it with plastic wrap, put it in a refrigerator, freeze it, then poke a few small holes in the plastic wrap wrapped around the culture dish, put the culture dish horizontally into a vacuum freeze dryer, take it out after freeze drying, and obtain polyester-PAN / PCL composite fiber aerogel.

5. The method for preparing a polyester-PAN / PCL composite fiber aerogel according to claim 4, characterized in that: Step 1 includes: Step 1.1: Pour PAN powder and MgO NPs into a sealed bottle with weighed DMF solvent and stir at 1700 r / min for 24 h to obtain a uniform PAN solution; Step 1.2: Pour PCL powder and DCM into a sealed bottle of DMF solvent and stir to obtain a uniform PCL solution; Step 1.3: The PAN solution prepared in step 1.1 is electrospun into a PAN nanofiber membrane, and the PCL solution prepared in step 1.2 is electrospun into a PCL nanofiber membrane.

6. The method for preparing a polyester-PAN / PCL composite fiber aerogel according to claim 5, characterized in that: In step 1.1, the mass ratio of PAN powder, DMF and MgO NPs is 6:43:1, and the mass fraction of PAN solution is 12%.

7. The method for preparing a polyester-PAN / PCL composite fiber aerogel according to claim 6, characterized in that: In step 1.2, the mass ratio of PCL powder, DMF and DCM is 5:6:14, and the mass fraction of PCL solution is 20%.

8. The method for preparing a polyester-PAN / PCL composite fiber aerogel according to claim 7, characterized in that: In step 1.3, stir at a speed of 1700 r / min for 24 h.

9. The method for preparing a polyester-PAN / PCL composite fiber aerogel according to claim 8, characterized in that: In step 2, the mass ratio of polyester fiber to PAN nanofiber membrane and PCL nanofiber membrane is 1:1 or 2:1, and the mass ratio of PAN nanofiber membrane to PCL nanofiber membrane is any ratio of 1:2, 2:1 or 1:

1.

10. The use of the polyester-PAN / PCL composite fiber aerogel according to any one of claims 1 to 3, characterized in that: Used for preparing air purification filter elements.